Meningkatkan Prestasi Belajar Mahasiswa Menggunakan Model Pembelajaran Kolaboratif dengan Pendekatan Blended Learning - Santhy Givend Pandie; Imanuel Yosafat Hadi Manapa (Universitas Indraprasta PGRI Jakarta, 2021)
Teaching-learning strategy (TLS) course learning activities are carried out in shifting as a result of the Covid-19 Pandemic. Shifting learning activities result in a reduction of the duration of face-to-face so that the need for students to study theory and carry out practices is not well accommodated. This has a direct impact on the decrease in student learning achievement. The purpose of this research is to improve student learning achievement and accommodate student needs using a collaborative learning model with a blended learning approach. Collaborative learning models are implemented in every learning activity both face-to-face and online. The blended learning approach is presented in learning activities that are learning theory done face-to-face while the practice is done online. This research was a class action study and conducted in three cycles. The results showed that there was an improvement in student learning achievement for each cycle. The application of learning models with this approach can accommodate the needs of students to learn theory and practice. It can be used as an alternative solution during the pandemic era with shifting learning activities.